2013
DOI: 10.1371/journal.pone.0068722
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bdnf Gene Deficiency to the Memory Impairment and Brain Pathology of APPswe/PS1dE9 Mouse Model of Alzheimer’s Disease

Abstract: Brain-derived neurotrophic factor (BDNF) importantly regulates learning and memory and supports the survival of injured neurons. Reduced BDNF levels have been detected in the brains of Alzheimer’s disease (AD) patients but the exact role of BDNF in the pathophysiology of the disorder remains obscure. We have recently shown that reduced signaling of BDNF receptor TrkB aggravates memory impairment in APPswe/PS1dE9 (APdE9) mice, a model of AD. The present study examined the influence of Bdnf gene deficiency (hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 51 publications
8
34
3
Order By: Relevance
“…6c) or WT mice (Fig. 6e and 6g) (Rantamäki et al 2013). Therefore, we determined whether BDNF was downregulated in the hippocampus of aged APP/PS1 mice.…”
Section: Resultsmentioning
confidence: 90%
“…6c) or WT mice (Fig. 6e and 6g) (Rantamäki et al 2013). Therefore, we determined whether BDNF was downregulated in the hippocampus of aged APP/PS1 mice.…”
Section: Resultsmentioning
confidence: 90%
“…Extensive literature exists of multiple transgenic mouse lines with increased or decreased BDNF signalling and behavioural phenotypes as models of various mood disorders (reviewed in Lindholm and Castren, 2014), demonstrating a tight link between BDNF levels and cognitive processes. Moreover, an exacerbation of memory impairments in a Morris water maze has been reported in APP/PS1 mice with a global decrease in BDNF (BDNF +/-mice) (Rantamaki et al, 2013). However in the present chapter, we demonstrated that knockdown of hippocampal BDNF in APP/PS1 mice did not result in a change in Y-maze performance compared to saline-injected transgenic controls.…”
Section: Discussioncontrasting
confidence: 58%
“…The authors of this work reported no increase in amyloid or tau pathology driven by the reduction of BDNF protein in these mice, however presynaptic markers such as synaptophysin were decreased (Castello et al, 2012). These results are supported by APP/PS1 x BDNF +/-mice which similarly showed no alteration in amyloid pathology but displayed exacerbated memory impairments in a Morris water maze task (Rantamaki et al, 2013). Interestingly, the latter study reported a possible mechanism by which Aβ might induce BDNF reduction -through BDNF protein sequestration into amyloid plaques (Rantamaki et al, 2013).…”
Section: Bdnf In Ad Causative Contributor or Consequence?supporting
confidence: 52%
See 2 more Smart Citations